PERSONAL NAMES AND NATIONAL IDENTITY - Babajanova Iqbol Salomaddinovna (Bright Mind Publishing, 2025)
This article analyzes the role of personal names (anthroponyms) in expressing national identity. As a significant layer of language, personal names reflect the historical, cultural, religious, and social values of a people. The article explores the naming conventions specific to the Uzbek anthroponymic system, their semantic and spiritual aspects, and their intrinsic connection with national consciousness and traditional customs. It also scientifically substantiates how the changes in personal names over different historical periods reflect the socio-political shifts in the nation's mentality. The onomastic richness of the Uzbek people is presented as an essential tool in preserving and strengthening national identity.
Keywords: Personal names, anthroponymy, national identity, onomastics, semantics, naming traditions, cultural heritage, folk mentality.